SOCIAL MOVEMENTS OBSERVATIONS IN VIRTUAL SPACE TOWARDS TAMANSARI RESIDENTS’ EVICTION BY THE BANDUNG CITY GOVERNMENT - Sekarwati, Sekarwati; Saleh, Fathurahman; Sukarno, Bilal (Journal of Social Political Sciences, 2023)
Land evictions by the government against urban slums (slum areas) have become one of the dilemma problems commonly encountered in big cities. This dilemma occurs when the government tries to beautify urban areas. On the other hand, displaced communities feel their rights are deprived only for the benefit of the government alone. In line with this, some people who do not accept often put-up resistance and manifest it into a social movement. Using the collective action frame theory of Benford and Snow, this paper tries to analyze one of the social movements in the case of land evictions that occurred, namely the Tamansari Melawan Movement, as a form of resistance against the Bandung City Government. Using ethnography studies, the data source referenced is Tamansari Melawan’s account on Instagram social media, and analysis was conducted on 995 posts and comments and used scientific literature sources such as books, journals, articles, and other literature that can be accounted for. This paper concludes that the core framing task, namely the diagnostic, prognostic, and motivational frame, has been found in the content of Tamansari against account uploads such as the attachment of the narrative of injustice carried out by the Bandung City Government, the demands that must be met by the Bandung City Government, to the invitation to join the Tamansari Melawan movement. The reaction and community impact that arises from the framing carried out by Tamansari Melawan also varies, ranging from moral support, space activation, student action, and studies to donation assistance